Rare Presentation of Diffuse Osteosclerosis in Acute Myeloid Leukaemia - Pradeepan, J.; Kumanan, T.; Chrishanthi, R.; Sooriyakumar, T.; Mathangi, N.; Abiramy, S. (The Jaffna Medical Association, 2025)
Diffuse osteosclerosis is a rare complication of hematological malignancies. While primary myelofibrosis and acute megakaryocytic leukemia are known associations, acute myeloid leukemia (AML) is rarely reported. We present a case of a 45-year-old male with disabling backache due to diffuse osteosclerosis and an underlying diagnosis of AML.
Keywords: Diffuse osteosclerosis; AML; Rare disease